2020
DOI: 10.24856/mem.v35i1.1335
|View full text |Cite
|
Sign up to set email alerts
|

The Attitudes toward Codes of Ethics: Do Cynicism and Religiosity Matters?

Abstract: <p>The prevalence of corporate transgressions in Indonesia have brought the moral standards of business leaders into public domain. In light of these phenomena, an investigation into whether prospective business leaders of the country are predisposed to moral values is crucial. The purpose of this research was to ascertain the attitudes of the Indonesian future business leaders towards the existence of codes of ethics in business. In particular, the research examined whether the religious orientation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Organizational cynicism is an internal thought which makes an individual unfriendly towards the organization as per his or her believe organizations are dishonest and will make fool of their employees (Nair & Kamalanabhan, 2010;Putranta, 2020). Basically, it is the personal negative thinking like distress, dissatisfaction and desperation about the management and organization (Özler et al, 2011;Karakaya, 2019).…”
Section: Organizational Cynicismmentioning
confidence: 99%
“…Organizational cynicism is an internal thought which makes an individual unfriendly towards the organization as per his or her believe organizations are dishonest and will make fool of their employees (Nair & Kamalanabhan, 2010;Putranta, 2020). Basically, it is the personal negative thinking like distress, dissatisfaction and desperation about the management and organization (Özler et al, 2011;Karakaya, 2019).…”
Section: Organizational Cynicismmentioning
confidence: 99%
“…David and Bernardo (2021) reported that it negatively influenced students' perceived academic control. A study further argued that it negatively affect attitudes towards codes of ethics as well as religiosity in students (Putranta, 2020) while another concluded that higher levels of social cynicism predicted lower levels of school belonging in university students (Li et al, 2020). Moule et al (2019) reported that cynicism increased the belief that police is too militarized.…”
Section: Introductionmentioning
confidence: 99%